2016
DOI: 10.1093/rheumatology/kew385
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of correlation and causes for discrepancy between quantitative and semi-quantitative Doppler scores in synovitis in rheumatoid arthritis

Abstract: Objectives. The aim of this study was to evaluate the association between two semi-quantitative Doppler US scoring systems (SQS), and the quantitative scoring (QS) of Doppler pixel count.Methods. Adult patients with RA and inadequate clinical response to anti-rheumatic therapy were examined with musculoskeletal US (MSUS). Dorsal MSUS of the wrists, MCP and MTP 2–5 were performed. MSUS images with sign of synovitis were collected and the QS was measured. Five assessors blinded to the QS evaluated the images ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…The ultrasound examinations included gray scale (GS) and power or color Doppler scored semiquantitatively on a four‐point scale (0 = no, 1 = minor, 2 = moderate, 3 = major presence of GS or Doppler) of 36 joints (wrists [radiocarpal, midcarpal, radioulnar joints scored separately], metacarpophalangeal 1‐5, proximal interphalangeal 2‐3, elbow, knee, tibiotalar, and metatarsophalangeal 1‐5 as well as the extensor carpi ulnaris and tibialis posterior tendons) according to Outcome Measures in Rheumatology (OMERACT) and the Norwegian ultrasound atlas (14,15). A sum score for all joints and tendons was calculated at the patient level separately for GS and for Doppler.…”
Section: Methodsmentioning
confidence: 99%
“…The ultrasound examinations included gray scale (GS) and power or color Doppler scored semiquantitatively on a four‐point scale (0 = no, 1 = minor, 2 = moderate, 3 = major presence of GS or Doppler) of 36 joints (wrists [radiocarpal, midcarpal, radioulnar joints scored separately], metacarpophalangeal 1‐5, proximal interphalangeal 2‐3, elbow, knee, tibiotalar, and metatarsophalangeal 1‐5 as well as the extensor carpi ulnaris and tibialis posterior tendons) according to Outcome Measures in Rheumatology (OMERACT) and the Norwegian ultrasound atlas (14,15). A sum score for all joints and tendons was calculated at the patient level separately for GS and for Doppler.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, ultrasound is used in clinical trials for assessing treatment response and remission. The components defining synovitis (synovial hypertrophy and hyperemia) are usually scored separately using a semi-quantitative scoring system (0–3) for indicating the grade of severity of the individual synovitis component [5]. In the recently published OMERACT-EULAR combined scoring system [1], it is suggested to apply the highest score of the two components as the final score for the joint.…”
Section: Introductionmentioning
confidence: 99%
“…For most of the patients, the symptoms of GA and Rheumatoid Arthritis(RA) are similar, so it is easy to ignore the condition and delay the optimal treatment time. Therefore, we also distinguished the two by the difference of biochemical indicators.Furthermore, principal component analysis (PCA), orthogonal partial least squares discrimination analysis (OPLS-DA), non-repetitive one-way ANOVA [18], correlation analysis [19] and multiple logistic regression analysis [20] were used to screen the important indicators affecting GA in each stage, and to distinguish GA and RA.Finally, multiple logistic regression was used to establish a clinical diagnosis model [21], so as to improve the success rate of clinical diagnosis and prediction.The overview of study design was indicated in Figure S1.…”
Section: Figure 1 Abridged General View Of the Evolution Of Gouty Armentioning
confidence: 99%